STUDY ON BUFFALO FATTENING USING AGRICULTURAL WASTE BASED FEEDING AT THE TANA TORAJA DISTRICT - Nurhayu, A.; Sariubang, Matheus; Ishak, Andi Baso L.; Natsir, Asmuddin (Proceeding Buffalo International Conference, 2013)
The study was conducted in the Tiromanda village, South Makale sub district, Tana Toraja district. The aim of the study was to measure the effect of providing agricultural waste based feeding to buffalo fattening. Fifteen male buffaloes, aged between 3 - 5 years with body weight ranging between 200 and 250 kg, were randomly assigned to one of three experimental diets, namely (A) 12 kg fermented rice straw + 2.5 kg concentrates; (B) 10 kg fermented rice straw + 5 kg concentrate and (C)control diet (ration typically used by the farmer) according to completely randomised design. Formulation of feed was based on agrricultural waste locally available, i.e. rice straw and concentrates. Determination of body weight was carried out every month for four months. The results showed that the average daily body weight gain (ADG) of buffaloes in the treatment B was the highest compared to that of the treatment A and C, namely 0.8 kg/head/day; 0.6 kg/head /day and 0.3 kg/head/day, respectively. Feed conversion ratio for each treatment was 31.6 (A), 14.87 (B), and 41.3(C). In conclusion, provision of feed based on agricultural waste such as rice straw plus concentrates increased body weight gain in fattening buffaloes.